What and How Students Feel During Open Class in Lesson Study: A Critical Analysis - Kurniati, Eka; Dafrita, Ivan Eldes; Afian, Tilal; Tanjung, Indayana Febriani; Ibrohim; Susilo, Herawati (Jurnal Biotek, 2025)
his research investigates what students feel during open class as part of the lesson study framework and how this affects their learning experience. A descriptive quantitative method was employed in this study. The primary data were obtained from questionnaires that aimed to understand the factors in three components: students' comfort during lesson study, students' perceptions of teachers' performance on teaching and learning, and students' achievement during lesson study. The participants were 21 tenth-grade students from SMA Negeri 8 Malang, East Java, Indonesia, who took part in a biology lesson conducted through the lesson study approach. The results indicate that most students felt positively charged, with 70% feeling comfortable in open classes, 91% providing positive teacher performance feedback, and 93% feeling they had performed well. This study highlighted how lesson study can help create a reflective and cooperative learning culture that benefits all participants, including the teachers. Lesson study promotes a positive environment in the classroom that students see as conducive for engagement and actual learning through improved lesson planning, classroom management, and instructional delivery. The findings also emphasize the need to seek and find methods to increase student comfort and reduce negative emotions experienced by students during open classes. Future research is recommended to examine the long-term impacts of open-class experiences within the lesson study on students' academic motivation, emotional resilience, and learning outcomes.